Protein Intake and Functional Integrity in Aging: The Framingham Heart Study Offspring. (24th September 2018) - Hruby, Adela; Sahni, Shivani; Bolster, Douglas; Jacques, Paul F
Abstract: Background: Higher protein intake is linked to maintenance of muscle mass and strength, but few studies have related protein to physical function and disability in aging. Methods: In participants of the Framingham Heart Study Offspring, we examined associations between protein intake (g/d), estimated from food frequency questionnaires, and maintenance of functional integrity, as a functional integrity score based on responses to 17 questions from Katz Activities of Daily Living, Nagi, and Rosow-Breslau questionnaires, repeated up to five times (1991/1995–2011/2014) over 23 years of follow-up. Cox proportional hazard models were used to estimate risk of incident loss of functional integrity (functional integrity score ≤ 15th percentile). Results: In 2, 917 participants (age 54.5 [9.8] years), baseline protein intake was 77.2 (15.6) g/d. The functional integrity score (baseline, mean 98.9, range 82.4–100.0) was associated with objective performance (gait speed, grip strength) and lower odds of falls, fractures, and frailty. Across follow-up, there were 731 incident cases of loss of functional integrity. In fully adjusted models, participants in the highest category of protein intake (median 92.2 g/d) had 30% lower risk of loss of functional integrity (hazard ratio [95% confidence interval] 0.70 [0.52, 0.95], p trend = .03), versus those with the lowest intake (median 64.4 g/d). However, sex-stratified analyses indicated the association was driven by the association in women alone (hazard ratio [95% confidence interval] 0.49 [0.32, 0.74], p trend = .002) and was nonsignificant in men (hazard ratio [95% confidence interval] 1.14 [0.70, 1.86], p trend = .59). Conclusions: Higher protein intake was beneficially associated with maintenance of physical function in middle-aged, high-functioning U.S. adults over the span of two decades. This association was particularly evident in women.